PENEGAKAN PERATURAN DAERAH NOMOR 10 TAHUN 2013 TENTANG KAWASAN TANPA ROKOK DI KABUPATEN PANGKAJENE DAN KEPULAUAN PROVINSI SULAWESI SELATAN - Muhammad Fuad Syafaat; Lalu Satria Utama (Journal of Innovation Research and Knowledge, 2025)
Smoking behavior, which still occurs frequently in public spaces, poses a potential health risk to both active and passive smokers. Despite the existence of regulations to reduce smoking prevalence, many people continue to smoke in public areas, further deteriorating public health. Purpose: This study aims to analyze and describe the efforts and challenges in enforcing Regional Regulation No. 10 of 2013 regarding Smoke-Free Areas in Pangkajene and Kepulauan Regency and to identify the obstacles encountered during its implementation. Method: This study employs a descriptive qualitative method with an inductive approach, based on Soerjono Soekanto’s law enforcement theory, which includes five key factors: the law itself, law enforcement officers, facilities, society, and culture. The informants in this study include Satpol PP, the Health Office, business owners, school principals, and local communities. Results/Findings: Enforcement of the Smoke-Free Area regulation in Pangkajene and Kepulauan Regency has not been maximized. The main challenges identified include the lack of PPNS personnel, limited facilities such as warning signs, and low public legal awareness. However, efforts to improve coordination between agencies and ongoing socialization are showing positive results. Conclusion: Enforcement of Regional Regulation No. 10 of 2013 regarding Smoke-Free Areas faces challenges, particularly in human resources and facilities. Strengthening inter-agency coordination and raising public awareness are crucial for the successful implementation of this policy